Campanhas públicas de vacinação e filosofia da tecnologia - Casas, Trazíbulo Henrique Pardo (2020)
The paper is a critical approach to vaccination technology, specifically public vaccination campaigns, with theoretical support of technology philosophy. From the question ‘What is a technology?’, when encounter technology as a multi-faceted reality, present the first specific productions of the philosophy of technology, since a philosophy of technology in tools and weapons are understood as different types of organ projections to methodology of technology philosophy that advocates the presence of an “innerwork” that brings to the inventor's mind a set of “pre- applied solutions to technical problems.” Even before the existence of the philosophy of technology as an academic discipline, some publications contributed for reflection in the area and whether they were used as reference texts. Qualitative methodological procedures were ádopted, promoted through a bibliographic review supported by a series of philosophers. This ánálysis presents as a result of reflections and questions about public vaccination campaigns. against measles and that a larger ranger or that is a technology of vaccines and clarifications about positioning, for example, in adopting a public health strategy that controls a certain prophylaxis or in seeking full peace of mind for the citizen.